ANALISIS PERTANGGUNGJAWABAN PIDANA BAGI PELAKU YANG DIDUGA TURUT MELAKUKAN (MEDEPLEGER) DALAM PERKARA TINDAK PIDANA KORUPSI KASUS PENGADILAN NEGERI JAKARTA PUSAT PUTUSAN NOMOR : 22/PID.SUS-TPK/2020/PN.JKT.PST - Muhammad Fadhil Andika Ramadhan; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2021)
Criminal Law is contained in the Criminal Code regulations as well as those contained in special laws outside the Criminal Code. The arrangement and determination of the medepleger in the decision number 22/Pid.Sus-Tipikor/2020/Pn.Jkt.Pst. the judge did not determine the punishment even though the medepleger criminal code is known in Article 55 of the Criminal Code. Furthermore, the research method used is normative research and the research approach used is the law and case approach. The results of the study indicate that the regulation regarding medepleger is considered to be still not good, because in practice there are still problems in determining whether a person's actions are included in participation or not, so it is necessary to regulate the provisions of guidelines for implementing the act of participating in doing. Determination of people who participate in the justice system in Indonesia has started since there are people who are suspected of being perpetrators of criminal acts and there is preliminary evidence obtained from the results of investigations conducted by law enforcement officers. Several criminal elements were found in the Primary indictment, including elements with the intention of benefiting oneself or others, elements of abusing power, forcing someone not to do or allowing something and elements of doing or participating in doing something. The panel of judges in determining the act of participating in the decision can also consider other aspects that contain concrete things that can clarify a problem.